Improving the Availability of Valuable Coconut Germplasm using Tissue Culture Techniques - Adkins, Steve; Nguyen, Quang Thien; Foale, Mike (International Coconut Community, 2016)
Coconut cultivation faces a number of acute problems that reduce its productivity and competitiveness. These problems include various biotic and abiotic challenges as well as an unstable market for its traditional oil-based products. Around 10 million small-holder farmers cultivate coconut palms worldwide on c. 12 million hectares of land, and many more people own a few coconut palms that contribute to their livelihoods. Inefficiency in the production and supply of appropriate seedlings for replanting a generally ageing resource remains an issue, especially where there is uncertainty about the ability of local populations to resist potential disease threats. However, tissue culture in such cases is expected to provide pragmatic solutions. Over the past 60 years much research has been directed towards developing and improving protocols for (i) embryo culture; (ii) clonal propagation via somatic embryogenesis and (iii) germplasm conservation via cryopreservation. Recent advances have provided new ways to improve these protocols, especially cryopreservation. Although effective embryo culture and cryopreservation are now possible, the low efficiency of conversion of somatic embryos to ex vitro seedlings still restrains the large-scale clonal propagation of coconut. Although tissue culture in coconut has developed over the recent decades, further improvement of protocols and their application to a wider range of germplasm will boost their adoption for the breeding, conservation and propagation of coconut.